2019
DOI: 10.1021/acsanm.9b00007
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Films of Graphene Nanoplatelets and Gold Nanoparticles for Methyl Parathion Sensing

Abstract: The wide use of pesticides in agriculture makes necessary the development of cost-effective, easy, and rapid methods aiming for environmental and health protection. We propose the fabrication and investigation of layer-by-layer (LbL) films composed of reduced graphene oxide stabilized in polyelectrolytes in the presence and absence of gold nanoparticles (AuNPs) toward methyl parathion (MP) detection. In addition to the film assembly and sensing application, we performed a systematic investigation of the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Additional data are shown in Figures S10 and S11 in the Supplementary Information. The LOD was calculated similarly to recent literature [37][38][39][40][41] as LOD = (3 × σ)/b, where σ is the standard deviation, and b is the slope of the calibration curve (linear fit). Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Additional data are shown in Figures S10 and S11 in the Supplementary Information. The LOD was calculated similarly to recent literature [37][38][39][40][41] as LOD = (3 × σ)/b, where σ is the standard deviation, and b is the slope of the calibration curve (linear fit). Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of LbL films based on the functionalized rGO (graphene) nanopellets and AuNPs for the detection of pesticide-methyl parathion was reported by Rodrigues et al [66]. The used rGO (graphene) nanoplatelets were stabilized in PDDA or PSS to obtain a positive or a negative charge of the rGO, respectively.…”
Section: Multilayer Film Consisting Of Two or More Multilayer Films Me And Meo Nps As A Layermentioning
confidence: 99%
“…authors revealed the potential utilization of these electrodes in microfluidic devices for the determination of various species based on the change in conductivity. The fabrication of LbL films based on the functionalized rGO (graphene) nanopellets and AuNPs for the detection of pesticide-methyl parathion was reported by Rodrigues et al [66]. The used rGO (graphene) nanoplatelets were stabilized in PDDA or PSS to obtain a positive or a negative charge of the rGO, respectively.…”
Section: Carbon-based Nanomaterials As a Layermentioning
confidence: 99%
“…Gold nanoparticles (Au NPs) have attracted enormous scientific and technological interest due to their ease of synthesis, chemical stability, unique optical properties, and biocompatibility These unique particles with sizes comparable to those of cellular structures enable the development of more applications such as optical tomography imaging and the use of tracers to detect DNA. , Also, their unique optical properties provide the potential for developing artificial tissues in ophthalmic therapeutic applications due to their unique plasmon effect . However, it is still necessary to study their dispersity in size, shape, and distribution, which result in monodisperse Au NPs in different sizes.…”
Section: Introductionmentioning
confidence: 99%